CURRENT STATUS OF TREATMENT FOR CESAREAN SCAR PREGNANCY USING VACUUM ASPIRATION AT HANOI OBSTETRICS AND GYNECOLOGY HOSPITAL, 2024–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to describe the clinical and paraclinical characteristics and evaluate the treatment outcomes of cesarean scar pregnancy (CSP) managed by ultrasound-guided vacuum aspiration at Hanoi Obstetrics and Gynecology Hospital during 2024–2025.Subjects and Methods: A retrospective descriptive study was conducted on 70 patients diagnosed with CSP and treated by vacuum aspiration at Department A5, Hanoi Obstetrics and Gynecology Hospital, from January 2024 to June 2025. Case selection followed RCOG diagnostic criteria, confirmed by transvaginal ultrasonography and serum βhCG quantification. Data were collected from medical records and analyzed using SPSS version 26.0.Results: The mean age was 34.6 ± 4.79 years. Most patients had a history of two cesarean sections (57.1%) and were diagnosed at 7–8 weeks of gestation (74.3%). Common symptoms included missed menstruation (68.6%) and abnormal vaginal bleeding (64.3%). On ultrasound, 94.3% of gestational sacs were implanted at the previous cesarean scar, 78.6% showed increased vascularity. Regarding treatment outcomes, 90.0% of cases achieved complete evacuation immediately. Serum βhCG levels decreased significantly after 48 hours. The procedure was safe with no complications in 97.1% of cases; only 1.4% required open surgery for hemostasis and 1.4% required hysterectomy. The most common hospital stay was ≤ 3 days (47.1%).Conclusion: Ultrasound-guided vacuum aspiration is a safe and highly effective treatment for early-stage cesarean scar pregnancy, allowing good hemorrhage control, shorter hospitalization, and preservation of reproductive function. Early diagnosis by transvaginal ultrasonography in women with a history of cesarean delivery plays a crucial role in prognosis and in selecting the optimal treatment strategy.
Keywords: cesarean scar pregnancy, vacuum aspiration, transvaginal ultrasonography, βhCG, uterine preservation.